Contribution of sleep disturbances to fatigue in multiple sclerosis: a prospective study using clinical and polysomnographic parameters. (30th June 2021) - Riccitelli, Gianna C.; Disanto, Giulio; Sacco, Rosaria; Sparasci, Davide; Sacco, Leonardo; Castelnovo, Anna; Miano, Silvia; Manconi, Mauro; Gobbi, Claudio; Zecca, Chiara
Abstract: Background and purpose: Fatigue is amongst the most frequent and disabling symptoms of multiple sclerosis and a close relation between fatigue and sleep quality has been hypothesized. In this study the contribution of sleep disturbances measured by clinical and polysomnographic parameters to fatigue in multiple sclerosis was investigated. Methods: This was a prospective instrumental study performed at the Neurocenter of Southern Switzerland. Demographic data and clinical characteristics including fatigue (as measured by the modified fatigue impact scale [MFIS]), neurological disability, psychiatric symptoms, medications and sleep‐related variables were collected at baseline visit and by a home full‐night polysomnography. The associations between sleep‐related variables and the MFIS were tested using partial correlations adjusted by demographic and sleep‐unrelated clinical factors. Results: Seventy‐six patients were included in the study, of whom 53 (69.7%) had an MFIS ≥38 points (median 49.5, interquartile range 31.0–62.0). MFIS scores were positively associated with age, neurological disability, symptoms of depression and anxiety, and use of benzodiazepines and selective serotonin reuptake inhibitors. When adjusting for these variables, the presence of restless legs syndrome (RLS) ( r = 0.37, p = 0.005) and periodic leg movements index ( r = −0.33, p = 0.014) were associated with MFIS. Excessive daytime sleepiness, total sleep time, sleep efficiency, respiratory disturbances, and percentage of time spent in the different sleep stages (N1, N2, N3 and rapid eye movement) were not associated with fatigue. Conclusions: Multiple sclerosis patients with a diagnosis of RLS had significantly higher global fatigue scores compared to those without RLS. Future studies should investigate whether medical treatment of RLS can ameliorate fatigue. Abstract : Fatigue is amongst the most frequent and disabling symptoms of multiple sclerosis (MS), which is difficult to treat and negatively influences patients' quality of life. An investigation was done of whether clinical and polysomnographic measures of sleep quality influence fatigue in a large group of MS patients. It was observed that MS patients who also suffer from restless legs syndrome show significantly greater symptoms of fatigue, suggesting a potential causal link between these two entities and potential treatment implications.